2008
DOI: 10.1016/j.biopsych.2008.01.003
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Cerebellum in Schizophrenia

Abstract: For many years the cerebellum has been considered to serve as a coordinator of motor function. Likewise, for many years schizophrenia has been considered to be a disease that primarily affects the cerebrum. This review summarizes recent evidence that both these views must be revised in the light of emerging evidence about cerebellar function and the mechanisms of schizophrenia. Evidence indicating that the cerebellum plays a role in higher cortical functions is summarized. Evidence indicating that cerebellar a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

40
453
1
7

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 592 publications
(516 citation statements)
references
References 77 publications
40
453
1
7
Order By: Relevance
“…Our results in MeanTS, which is an expression of functional connectivity that is homogenous over the involved regions, also support the presence of subcortical‐to‐cortical connection associations in both directions. Under the rubric of specific functional brain networks or cortico‐subcortical feedback loops associated with neurodevelopment (i.e., the cortico‐cerebellar‐thalamic‐cortical circuit [CCTCC]; Andreasen & Pierson, 2008; Ullsperger, Danielmeier, & Jocham, 2014), the presence of both positive and negative associations between cortical and subcortical regions may be expected. Maturing feedback loops involving similar functions would show increasing connectivity with age, whereas those involved in different functions would show less age‐related functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Our results in MeanTS, which is an expression of functional connectivity that is homogenous over the involved regions, also support the presence of subcortical‐to‐cortical connection associations in both directions. Under the rubric of specific functional brain networks or cortico‐subcortical feedback loops associated with neurodevelopment (i.e., the cortico‐cerebellar‐thalamic‐cortical circuit [CCTCC]; Andreasen & Pierson, 2008; Ullsperger, Danielmeier, & Jocham, 2014), the presence of both positive and negative associations between cortical and subcortical regions may be expected. Maturing feedback loops involving similar functions would show increasing connectivity with age, whereas those involved in different functions would show less age‐related functional connectivity.…”
Section: Discussionmentioning
confidence: 99%
“…Association between greymatter heterogeneity and cerebellar volume has been observed in autism too (Radulescu et al, 2013) and therefore may be indexing a parallel neural system for which an aberrant neurodevelopmental trajectory is shared between schizophrenia and autism. Speculatively, the expression of social cognitive deficits and abnormal mental coordination (i.e., 'cognitive dysmetria'; Andreasen and Pierson 2008) in both these two disorders may arise from a common genetic basis (Psychiatric Genomics Consortium, 2013). Our findings in this study also broadly converge with those of an earlier study, which used different MRI textural features to differentiate the scans of patients with schizophrenia from those of controls (Kovalev et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It includes the cerebellum, pons, and medulla oblongata, which are structures that control functions as fundamental and diverse as respiration, heart rate, reflex, and voluntary movements. Impaired Hb development and function are associated with many disorders such as autism, ADHD (attention deficit hyperactivity disorder), schizophrenia, cerebral palsy, and various sleep disorders (Berquin et al 1998;Aston-Jones 2005;Andreasen and Pierson 2008). As with other complex diseases and phenotypes, most variants identified by genome-wide association and sequencing population studies are found in noncoding regions of the genome, and therefore suspected to play a role in regulatory control (Cooper and Shendure 2011).…”
Section: [Supplemental Materials Is Available For This Article]mentioning
confidence: 99%